2011
DOI: 10.1007/s11095-011-0383-z
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Explore the Impact of Freeze-Thaw Cycling on Protein Structure: Hydrogen/Deuterium Exchange Mass Spectrometry (HX-MS)

Abstract: Results indicate freezing preferentially disturbs local structure at the surface residues, consistent with ice-solution interface-mediated denaturation mechanism. F/T-induced aggregation begins as partial denaturation during freezing, but is accompanied by more comprehensive structural rearrangement during F/T cycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…This agreed with the high structure stability of antibody molecule against the freezing stress described above. In a previous study, we have also demonstrated that labile protein such as LDH with low structure stability to the freezing stress would accordingly produce non-native aggregates consisting of more unfolded monomers after F/T cycles (28). For antibody aggregation caused by F/T stress, similar conclusion has also been made for a different antibody in a different study (8), but the evidence was based on the analysis of global antibody structure by CD and FTIR.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This agreed with the high structure stability of antibody molecule against the freezing stress described above. In a previous study, we have also demonstrated that labile protein such as LDH with low structure stability to the freezing stress would accordingly produce non-native aggregates consisting of more unfolded monomers after F/T cycles (28). For antibody aggregation caused by F/T stress, similar conclusion has also been made for a different antibody in a different study (8), but the evidence was based on the analysis of global antibody structure by CD and FTIR.…”
Section: Discussionmentioning
confidence: 60%
“…The impact of freezing on Bevacizumab structure integrity was analyzed using the same HX-MS protocol in the frozen state as previously described (28). Figure 1a To further examine antibody stability against freezing stress, we increased the denaturing stress in the frozen state by adding 25 to 200 mM guanidine HCl to the initial sample solution.…”
Section: Hx Analysis Of Bevacizumab Structure In the Frozen Statementioning
confidence: 99%
“…15 Several groups have examined the protein-protein interfaces of irreversible antibody aggregates (i.e., dimers and oligomers) by HX-MS. For example, Zhang et al used HX-MS analysis of purified mAb aggregates to show that Fab-Fab interactions in the CDR region were generated as part of irreversible aggregate formation caused by heat exposure. 39 In addition to HX-MS, antibody aggregates have been characterized using other higher resolution techniques. For example, Deperalta et al used hydroxyl radical footprinting to map the interface region of an antibody dimer.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] For example, HX-MS has been recently applied to examine the effect of various solution factors and physicochemical structural changes on the local flexibility of mAbs, including salts from the Hofmeister series, 37 pharmaceutical excipients, 38 freeze-thaw cycles, 39 methionine oxidation, 40 asparagine deamidation, 41 antibody-drug conjugation, 42 deglycosylation and glycan modifications, 43 and engineered point mutations. 44 In this study, antibody clusters were characterized by a combination of DLS and chemical cross-linking experiments to determine the effect of solution conditions on the extent of RSA for an IgG1 mAb (referred to as "mAb-C") as a function of mAb-C protein concentration (1-10 mg/mL).…”
Section: Introductionmentioning
confidence: 99%
“…We were concerned with perturbing sample equilibrium with the nitrogen gas, as air-water interfaces can be highly denaturing [43]. Freezing can also influence protein structure [44]. Here, we used small samples in thin-walled capillaries, coupled with rapid immersion in liquid nitrogen to achieve rates of freezing that are primarily limited by the insulating properties of the silica and the Leidenfrost effect, which creates an insulating layer of nitrogen gas between the cryogenic liquid and the sample [45].…”
Section: Observations and An Improved Configurationmentioning
confidence: 99%